2000
DOI: 10.1084/jem.192.4.549
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis-Stimulated Proliferation Drives Naive T Cells to Differentiate Directly into Memory T Cells

Abstract: The developmental requirements for immunological memory, a central feature of adaptive immune responses, is largely obscure. We show that as naive CD8 T cells undergo homeostasis-driven proliferation in lymphopenic mice in the absence of overt antigenic stimulation, they progressively acquire phenotypic and functional characteristics of antigen-induced memory CD8 T cells. Thus, the homeostasis-induced memory CD8 T cells express typical memory cell markers, lyse target cells directly in vitro and in vivo, respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
464
6
5

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 481 publications
(515 citation statements)
references
References 38 publications
(54 reference statements)
40
464
6
5
Order By: Relevance
“…It has long been observed that transfer of small numbers of T cells into lymphopenic hosts results in T-cell expansion, a process described as homeostatic proliferation [9][10][11][12][13][14][15][16]. As the T cells proliferate, they assume an Ag-experienced or memory phenotype, which is indicated by upregulation of CD44, Ly6C and CD122 (IL-2-IL-15Rβ) [12,15].…”
Section: A Link Between Lymphodepletion and Augmented Immune Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has long been observed that transfer of small numbers of T cells into lymphopenic hosts results in T-cell expansion, a process described as homeostatic proliferation [9][10][11][12][13][14][15][16]. As the T cells proliferate, they assume an Ag-experienced or memory phenotype, which is indicated by upregulation of CD44, Ly6C and CD122 (IL-2-IL-15Rβ) [12,15].…”
Section: A Link Between Lymphodepletion and Augmented Immune Functionmentioning
confidence: 99%
“…As the T cells proliferate, they assume an Ag-experienced or memory phenotype, which is indicated by upregulation of CD44, Ly6C and CD122 (IL-2-IL-15Rβ) [12,15]. This T-cell expansion and acquisition of a memory phenotype is also associated with enhanced effector functions, determined by ex vivo analysis of interferon-γ (IFN-γ) release and cytolysis [12,14,15].…”
Section: A Link Between Lymphodepletion and Augmented Immune Functionmentioning
confidence: 99%
See 3 more Smart Citations